Immunoinflammatory diseases of the central nervous system – the tale of two cytokines - Hofer, M J (Br J Pharmacol, 2015)
Cytokines are potent mediators of cellular communication that have crucial roles in the regulation of innate and adaptive immunoinflammatory responses. Clear evidence has emerged in recent years that the dysregulated production of cytokines may in itself be causative in the pathogenesis of certain immunoinflammatory disorders. Here we review current evidence for the involvement of two different cytokines, IFN‐α and IL‐6, as principal mediators of specific immunoinflammatory disorders of the CNS. IFN‐α belongs to the type I IFN family and is causally linked to the development of inflammatory encephalopathy exemplified by the genetic disorder, Aicardi–Goutières syndrome. IL‐6 belongs to the gp130 family of cytokines and is causally linked to a number of immunoinflammatory disorders of the CNS including neuromyelitis optica, idiopathic transverse myelitis and genetically linked autoinflammatory neurological disease. In addition to clinical evidence, experimental studies, particularly in genetically engineered mouse models with astrocyte‐targeted, CNS‐restricted production of IFN‐α or IL‐6 replicate many of the cardinal neuropathological features of these human cytokine‐linked immunoinflammatory neurological disorders giving crucial evidence for a direct causative role of these cytokines and providing further rationale for the therapeutic targeting of these cytokines in neurological diseases where indicated. LINKED ARTICLES: This article is part of a themed section on Inflammation: maladies, models, mechanisms and molecules. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2016.173.issue-4